2000
DOI: 10.1139/f00-006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female attributes and egg properties on offspring viability in a rheophilic cyprinid, Chondrostoma nasus

Abstract: Intraspecific differences in female attributes influence egg quality and, as a consequence, offspring viability. To further investigate this hypothesis, we compared female attributes, egg size, biochemical egg composition, and survival potential of offspring from 20 female spawners of an endangered rheophilic cyprinid, Chondrostoma nasus. Egg size was strongly related to female age and size. The chemical composition of egg dry matter was influenced by female size to a lesser extent. No significant relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…Paternal contributions were believed to have only a limited influence on embryonic development and larval fitness traits in fishes as compared to maternal contributions (Keckeis et al, 2000;Marteinsdottir and Begg, 2002). Paternal contributions to progeny are solely the product of nuclear-genetic material from the spermatozoon (Rideout et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Paternal contributions were believed to have only a limited influence on embryonic development and larval fitness traits in fishes as compared to maternal contributions (Keckeis et al, 2000;Marteinsdottir and Begg, 2002). Paternal contributions to progeny are solely the product of nuclear-genetic material from the spermatozoon (Rideout et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that environmental variables are the main determinants of ichthyoplankton abundance, structure and composition variation (Keckeis et al, 2000;Reynalte-Tataje et al, 2012). However, the effect of dams on the ichthyoplankton community is rarely investigated (Humphries & Lake, 2000;Sanches et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Paternal factors are believed to have only limited influence, as maternal contributions via the egg are commonly cited as the chief determinants of embryonic and larval fitness (Blaxter & Hempel 1963, Buckley et al 1991, Keckeis et al 2000, Marteinsdottir & Begg 2002. This restricted perspective of male influence, however, has come under increasing scrutiny (Trippel 2003, Rideout et al 2004.…”
Section: Introductionmentioning
confidence: 99%